1987
DOI: 10.1021/bi00383a003
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the high-affinity binding site for noncompetitive blockers of the acetylcholine receptor: [3H]chlorpromazine labels homologous residues in the .beta. and .delta. chains

Abstract: The membrane-bound acetylcholine receptor from Torpedo marmorata was photolabeled by the noncompetitive channel blocker [3H]chlorpromazine under equilibrium conditions in the presence of the agonist carbamoylcholine. The amount of radioactivity incorporated into all subunits was reduced by addition of phencyclidine, a specific ligand for the high-affinity site for noncompetitive blockers. The labeled p chain was purified and digested with trypsin or CNBr, and the resulting fragments were fractionated by high-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
108
0
2

Year Published

1988
1988
2007
2007

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 233 publications
(122 citation statements)
references
References 40 publications
12
108
0
2
Order By: Relevance
“…The affinity-labelling data obtained with [ 3 H]chlorpromazine (Giraudat et al , 1987(Giraudat et al , 1989Revah et al 1990) and TPMP , thus support the view that: (1) .DSG-EK MTLSISVLLSLTVFLLVIV E..…”
Section: The Mil Segment Is a Component Of The Ion Channelsupporting
confidence: 72%
See 3 more Smart Citations
“…The affinity-labelling data obtained with [ 3 H]chlorpromazine (Giraudat et al , 1987(Giraudat et al , 1989Revah et al 1990) and TPMP , thus support the view that: (1) .DSG-EK MTLSISVLLSLTVFLLVIV E..…”
Section: The Mil Segment Is a Component Of The Ion Channelsupporting
confidence: 72%
“…5); such disposition supports an organization of Mil into an a-helix, the a-carbons of the labelled amino acids being aligned on the same meridian on adjacent turns of the helix (Giraudat et al 1987;Revah et al 1990). Pedersen & Cohen (19906) have used another noncompetitive blocker, a mustard derivative of meproadifen to affinity label the a-subunit amino acid GIU262, an amino acid belonging to the ' outer ring of negatively charged residues' (Figs 4, 5 and see below) located at the border of the Mil segment in the region linking Mil and M i l l .…”
Section: Architecture Of the Acetylcholine Nicotinic Receptormentioning
confidence: 61%
See 2 more Smart Citations
“…Sequence analysis resulted in the identification of Ser-248 as a major residue labeled by pH]chlorpromazine in a phencyclidine-sensitive manner. This residue is located in the hydrophobic and putative transmembrane segment M2 of the ~t-subunit, a region homologous to that containing the chlorpromazine-labeled Ser-262 in the Nchain [1] and the Ser-254 and Leu-257 in the//-chain [2]. Extended sequence analysis of the hydrophobic segment M 1 further showed that no labeling.occurred in this region.…”
mentioning
confidence: 99%